SPATIALITIES AND TEMPORALITIES OF THE GALICIAN PRESENCE IN THE CITY OF SALVADOR - Brandão, Paulo Roberto Baqueiro (Revista do Departamento de Geografia, 2011)
This paper analyses the ways of spatial articulation of the Galician community of Salvador between 1853, when Spain authorized the immigration of its citizens, and 2000, when it was inaugurated a monument that represents the Galician presence in the city, located on the shore and denominated the Galician cross. This paper also intends to contribute to the Historical Geography. It was necessary to divide the study into periods, which can better express the rhythm and strategies of the intra-urban spaces of Salvador. It also aims to consider the means by which the members of the Galician community of Salvador produced their own spatialities and temporalities in consonance with universal rhythms of human existence, most of the time understood only when considered the particular reality of these immigrants.